Implementing Growth Mindset in Mathematics Learning: an Analysis of Correlation Lesson Practices in Grade 11 Classrooms - Kartikawati, Wahyu; Zulfaidany, Syelvira Nova; Aulyafani, Risma Ardhelisa; Nafisa, Tiara Mastura; Nuraini, Risna; Maharani, Yaroidah; Lestari, Indah Ayu; Faradiba, Surya Sari (FKIP Universitas Wisnuwardhana, 2026)
This study aims to explore how a growth mindset is implicitly fostered in mathematics learning through the classroom practices of pre-service mathematics teachers. Using a descriptive qualitative approach, this study specifically employed thematic analysis to identify patterns of social interaction and the natural processes of learning. Primary data were sourced from transcripts of classroom interactions conducted by pre-service mathematics teachers on correlation analysis in grade 11. The analysis revealed that elements of a growth mindset were consistently integrated into teacher-student interactions, with teachers playing a central role through motivation, structured scaffolding, constructive feedback, and error normalization strategies. The primary contribution of this study lies in demonstrating that developing students' growth mindsets does not have to be achieved through rigid theoretical introductions but can be effectively internalized through everyday classroom discourse. This study concludes that growth mindset can be effectively fostered through everyday classroom practices, even without being explicitly introduced as a theoretical concept. This study recommends the development of systematic instructional designs on various mathematics topics to create a learning culture that is resilient to cognitive challenges.